Análise dos processos erosivos no município de Sarandi/PR - Toy, Elton Eidy (2010)
Going against the orderly urban growth are a number of factors that must be thought before the deployment of infrastructure or even the non-implementation of certain equipment within the context of a city. With Sarandi / PR is not different, then the consequences of a disordered occupation can be found in the daily population of a young city located in the north Parana, the operation of real estate activity dictated the trends of urban sprawl, creating the whole context in that it falls to the present day. Quality of life is directly connected to the middle, so planning is necessary for sustainable growth, providing conditions for a city caters adequately for your demands. The main objective of this study was to analyze the erosion of the city of Sarandi / PR. It was seen that the human action brought significant impacts on the environment and result in drastic quality of life of householders, the man as an antagonist of the man himself.